PMO-056 Laparoscopic banded (silastic ring) sleeve gastrectomy: medium term outcomes. (28th May 2012) - Clarke, M; Pearless, L; Booth, M
Abstract : Introduction: Placement of a band of human dermis around the sleeve gastrectomy (SG) has previously been described to prevent late dilatation and weight regain. The aim of this study was to report our experience using a silastic ring placed around the SG. Methods: 53 patients (male 15%, female 85%) with a mean (range) age of 46 (23–65) years and mean (SD) preoperative BMI of 37.6 (5.3) kg/m 2 underwent surgery between November 2006 and February 2010. The stomach was divided 3cm proximal to the pylorus. Orogastric bougie diameter was 36 French (November 2006–June 2008) or 32 Fr (thereafter). A 6.5–7 cm diameter silastic ring was placed around the mid-portion of the SG. A retrospective analysis was performed. Results: All procedures were completed laparoscopically. Follow-up at 6 months, 1, 2 and 3 years was 96%, 92%, 87% and 47% respectively. Mean (SD) % excess weight loss at these time periods was 81.4 (25.6), 102.1 (27.3), 108.7 (38.2) and 97.5 (29.1) respectively. Mean (SD) weight loss at 2 years was 34.2(19.3) kg. 83% of patients demonstrated partial or complete resolution of their preoperative comorbidities including hypertension, diabetes, sleep apnoea and hyperlipidaemia. 17% developed new-onset reflux. 53% of patients required vitamin supplementation. Complications: Wound infection (1.8%), food bolus obstruction requiring endoscopy (3.8%) and silastic ring removal for food intolerance (7.5%). There were no deaths. Conclusion: While the banded (silastic ring) SG is a safe procedure with good medium term excess weight loss and comorbidity resolution, around 11% of patients required endoscopic or surgical reintervention within 3 years. Competing interests: None declared.